An investigation into phosphoric iron production in Eastern England - Hall, Neil Stewart (2017)
Looking at iron slags from Eastern England, this thesis was designed to assess the possibility of inferring the ore type in use by the chemical composition of the slag. A number of case studies are examined. The first is a group of material from the Foulness Valley, East Yorkshire, which is known to be produced from high phosphorus bog ore. This allows direct comparison between this and other assemblages, based on phosphorus content, to infer if bog or bedded ore was in use. Assemblages from Iron Age East Yorkshire, Roman Caistor St Edmund and the Saxon sites of Quarrington and Flixboroughwere examined to infer on ore exploitation and possible metal production.